Administrative Court Jurisdiction over Election Disputes and Factual Actions Following the Government Administration Act - Irmanjaya Thaher; Freddy Harris (Hakamain: Journal of Sharia and Law Studies, 2024)
This study examines the limits of the Administrative Court’s absolute jurisdiction over election disputes and factual administrative actions following the enactment of Indonesia’s Government Administration Act. The research analyzes how the expansion of administrative jurisdiction has influenced the adjudication of election-related disputes and the legal certainty surrounding the division of authority among judicial institutions. Employing a normative legal research method, the study adopts statutory, conceptual, and case approaches by examining the 1945 Constitution, the Government Administration Act, election laws, Supreme Court regulations, Constitutional Court decisions, and relevant judicial precedents. The findings reveal that although the Government Administration Act broadened judicial review over administrative actions, its implementation has generated overlapping jurisdiction between the Administrative Court, the Constitutional Court, and other electoral dispute resolution bodies. The inclusion of factual administrative actions within judicial review has further complicated the determination of jurisdiction in election cases, particularly where administrative decisions intersect with constitutional and electoral processes. This ambiguity has resulted in inconsistent judicial interpretations and procedural uncertainty, potentially undermining effective legal protection and democratic governance. The study argues that clearer jurisdictional boundaries are necessary to distinguish election administrative disputes from constitutional and political disputes while ensuring coherent coordination among judicial institutions. Legislative refinement, harmonization of procedural regulations, and consistent judicial interpretation are essential to strengthen legal certainty and prevent conflicting decisions. Ultimately, clarifying the Administrative Court’s jurisdiction would improve the effectiveness of electoral justice, reinforce the rule of law, and support a more accountable and transparent system of election administration consistent with Indonesia’s constitutional framework.